2020
DOI: 10.1186/s40104-020-0431-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, oxidative stress and immune status of newly weaned pigs fed peroxidized lipids with or without supplemental vitamin E or polyphenols

Abstract: Background: This study evaluated the use of dietary vitamin E and polyphenols on growth, immune and oxidative status of weaned pigs fed peroxidized lipids. A total of 192 piglets (21 days of age and body weight of 6.62 ± 1.04 kg) were assigned within sex and weight blocks to a 2 × 3 factorial arrangement using 48 pens with 4 pigs per pen. Dietary treatments consisted of lipid peroxidation (6% edible soybean oil or 6% peroxidized soybean oil), and antioxidant supplementation (control diet containing 33 IU/kg DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 48 publications
4
19
0
Order By: Relevance
“…Consistent with these observations, our study showed that DON-challenged piglets exhibited elevated MDA levels and decreased GSH, T-SOD and T-AOC levels in the jejunum. Polyphenols have been shown to exert antioxidative effects in intestinal epithelial cell culture and weaned piglet studies [ 13 15 , 34 , 39 ]. Consistent with these findings, the results in the present study showed that supplementation with RES suppressed MDA levels while increasing T-SOD and T-AOC contents.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these observations, our study showed that DON-challenged piglets exhibited elevated MDA levels and decreased GSH, T-SOD and T-AOC levels in the jejunum. Polyphenols have been shown to exert antioxidative effects in intestinal epithelial cell culture and weaned piglet studies [ 13 15 , 34 , 39 ]. Consistent with these findings, the results in the present study showed that supplementation with RES suppressed MDA levels while increasing T-SOD and T-AOC contents.…”
Section: Discussionmentioning
confidence: 99%
“…However, the higher ADG and G:F ratio of the LRCT and CRSW piglets indicated benefits of ω3 enriched diet and seaweed supplementation on stimulating antioxidants to reduce excessive ROS production, therefore, improving piglets' growth performance. Growth performance reflects overall influences over a period, whereas plasma measurements are a single test at a time point [57]. Moreover, this improvement can be explained by the bioactivity of ω3 PUFAs in the maternal diet and seaweed-derived elements (i.e., ascophyllan, laminarin, fucoidans, and phlorotannins) in the post-weaning piglet diet [58].…”
Section: Discussionmentioning
confidence: 99%
“…Comparable results were reported by Silva-Guillen et al (2020) when feeding 6% peroxidized soybean oil to nursery pigs. The authors reported decreased growth, T-AOC, serum vitamin E and MDA and increased protein carbonyl [ 91 ]. In addition, Kerr et al (2020) reported that feeding 10% thermally oxidized soybean oil at different temperatures and times, to weaned piglets increased oxidative distress as measured by markers of lipid damage (serum and urinary F2-ISP concentration and urinary ISP excretion) but had no effect on energy, lipid, N digestibility or intestinal permeability [ 89 ].…”
Section: Dietary Oxidative Distress Challenges Models In Poultry Swine and Fishmentioning
confidence: 99%